Effect of Professional Development Programme on the Attitudes of Pre-service Teachers towards Students with Special Needs - Parua, R. K. (JOURNAL OF INDIAN EDUCATION, 2012)
For effective inclusion of students with special needs in general education classrooms, the teacher educators’ community must overcome barriers toward inclusion, including existing attitudes. The purpose of this study was to determine the effects of professional development programme on the attitudes of pre-service teachers toward students with special needs. The intervention programme was conducted in six weeks for the pre-service teachers. The sample consisted of 42 pre-service teachers studying bachelor degree programme of special education. Results provided evidence that after receiving professional development programme, pre-service teachers had positive attitudes towards students with special needs. The overall findings suggest that this programme had significant effect on changing the attitude of pre-service teachers towards students with special needs with respect to all the four aspects, i.e. academic, cognitive, emotional and social development of the students.